An Accessible Alternative to Melarsomine: “Moxi-Doxy” for Treatment of Adult Heartworm Infection in Dogs - Jacobson, Linda S.; DiGangi, Brian A. (Frontiers in Veterinary Science, 2021)
Canine heartworm infection, caused by the filarial parasite Dirofilaria immitis, represents a serious and expanding animal welfare concern that is expected to increase due to the effects of climate change and the COVID-19 pandemic. A body of evidence has emerged to support the use of a non-arsenical adulticide treatment protocol, using moxidectin and doxycycline to kill adult heartworms over a prolonged period. While a three-dose protocol using the arsenical drug melarsomine is currently the safest and most effective treatment for heartworm infection, this drug is not available in some countries and is inaccessible for many owners and animal shelters. Moxidectin-doxycycline (moxi-doxy) provides a viable alternative to no treatment at all, in cases where arsenical treatment is not possible. Based on current evidence, the most effective non-arsenical treatment regimen is doxycycline 10 mg/kg PO q 12 or 24 h for 28 days, combined with topical moxidectin at label dose. Moxidectin is repeated monthly until no antigen detected (NAD) status is confirmed. Sustained release injectable moxidectin, in combination with doxycycline, may provide an alternative in remote regions or in settings where significant compliance or accessibility concerns exist, but more studies are needed. In moxi-doxy protocols, doxycycline should be repeated annually until NAD. This review summarizes the safety and efficacy of moxi-doxy, addresses controversies surrounding this treatment approach, and provides detailed recommendations for treatment regimens and post-treatment testing.